Răspunsuri

Cel mai inteligent răspuns!
2014-04-01T11:11:27+03:00
Ai ca (n+1)! - n! = n! x n( faci si tu un mic calcul!)

Conform acestei observatii => 2! - 1! = 
1! x 1;
                                            3! - 2! = 
2! x 2
                                            4! - 3! = 
3! x 3
                                            ....................
                                           (
n+1)! - n! = n! x n

                                          _________________
Aduni " in cascada" =>       (n+1)! - 1 =   1! x 1 + 2! x 2 + 3! x 3 +...+ n! x n;

Bafta!
2 5 2